2011
DOI: 10.5138/ijdd.2010.0975.0215.03057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Penetration Enhancer DMSO on In-Vitro Skin Permeation of Acyclovir Transdermal Microemulsion Formulation.

Abstract: The aim of this research was to enhance the flux of transdermal drug delivery by using penetration enhancers DMSO. Skin penetration enhancers have been used to improve bioavailability and increase the range of drugs for which topical and transdermal delivery is a viable option which penetrate into skin to reversibly decrease the barrier resistance. Penetration enhancing activity of dimethylsulphoxide (DMSO) at 5% w/w and 10% w/w concentration were determined in aqueous solution of ACV and in microemulsion form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
1
20
1
Order By: Relevance
“…This difference in molecular weight could be responsible for the poor penetration of this lipophilic molecule in our skin samples when dissolved in DMSO. In contrast, the differences in our experimental conditions (temperature, pH, application time, type of skin) with respect to the conditions used in other studies could also be responsible for the low penetration of C 12 Re(CO) 3 inside the skin [31][32][33][34][35]. Under these experimental conditions, this lipophilic molecule penetrates at higher concentrations when incorporated in bicosomes than dissolved in DMSO.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This difference in molecular weight could be responsible for the poor penetration of this lipophilic molecule in our skin samples when dissolved in DMSO. In contrast, the differences in our experimental conditions (temperature, pH, application time, type of skin) with respect to the conditions used in other studies could also be responsible for the low penetration of C 12 Re(CO) 3 inside the skin [31][32][33][34][35]. Under these experimental conditions, this lipophilic molecule penetrates at higher concentrations when incorporated in bicosomes than dissolved in DMSO.…”
Section: Discussioncontrasting
confidence: 53%
“…The incorporation of molecules in the skin depends on their molecular weights and shapes [30]. DMSO has demonstrated its ability to facilitate the penetration of many drugs, such as steroids or antibiotics among others [31][32][33][34][35]. All of them had weights below the molecular weight of C 12 Re(CO) 3 (620 g/mol).…”
Section: Discussionmentioning
confidence: 99%
“…DMSO can change keratine conformation of stratum corneum from α-helical conformation to β-sheet conformation [17]. DMSO increased flux of the drug with its interaction with lipid in stratum corneum and changed the peptide structure, and then caused a change of the partition coefficient (8). These changes indicated that DMSO can be a chemical enhancer that penetrated MPA into the skin membrane through the diffusion process.…”
Section: Lipid Protein Partitioning Theory Explains the Interaction Bmentioning
confidence: 99%
“…The main constituents are tripalmitin, triolein, tristearate, trilinolein, triarachidi, squalene, monostearate, tocopherol and b-sitosterol. Olive oil is a very potent fatty acid permeation enhancer [7] while DMSO is a chemical enhancer that act by disruption of the highly ordered lipids of the stratum corneum that can make enhancement drug across the skin mucosa [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently few papers have been reported by some researchers regarding ultrasonic and thermodynamic study of various drugs in different solvent medium and mix solvent medium. [2][3][4][5][6]But very little work has been done on the interaction of drug-amino acids. Amino acids are important biomolecules through which the drugs interact inside the body.…”
Section: Introduction:-mentioning
confidence: 99%